THE USE OF Pomacea canaliculata SNAILS IN FEED TO IMPROVE QUALITY OF ALABIO DUCK (Anas plathyrinchos Borneo) MEAT - Subhan, A.; Yuwanta, T.; Zuprizal, Z.; Supadmo, S. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
This research was aimed to improve the physical and chemical quality of Alabio ducks which was fed with Pomacea canaliculata snails. Those ducks were raised intensively. There were nine treatments  included R0 (control feed), R1 (control feed + 2.5% Pomacea canaliculata snails from swampy area), R2 (control feed + 5% Pomacea canaliculata snails from swampy area), R3 (control feed + 7.5% Pomacea canaliculata snails from swampy area) R4 (control feed + 10% Pomacea canaliculata snails from swampy area) R5 (control feed + 2.5% Pomacea canaliculata snails from tidal swampy area), R6 (control feed + 5% Pomacea canaliculata snails from tidal swampy area, R7 (control feed + 7.5% Pomacea canaliculata snails from tidal swampy area, and R8 (control feed + 10% Pomacea canaliculata snails from tidal swampy area. The variables observed included meat chemical and physical quality. A Completely Randomized Design was used in this study. Analysis of variance and Duncan’s multiple range test were used to analyze data. The research results revealed that using Pomacea canaliculata snails in duck feed had a significant effect (P<0.05) towards the physical characteristics (water holding capacity, cooking loss, and tenderness), and chemical characteristics of Alabio duck meat (water, protein, collagen, fat, and cholesterol content). However, there was no significant effect towards meat pH. It can be concluded that using 5% Pomacea canaliculata snails in a mixture of Alabio duck feed decreased cooking loss and meat cholesterol content.